(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the process of training students of Technology Science, 3-dimensional graphics programs (3D graphics programs) play an important role. This article will bring ways to improve the methodology for using 3D graphics programs. In the educational process, the advantages and pedagogical effectiveness of the application of these programs are analyzed.